HSPB1 Enhances SIRT2-Mediated G6PD Activation and Promotes Glioma Cell Proliferation. - Hongxing Ye; Hongguang Huang; Fei Cao; Mantao Chen; Xiujue Zheng; Renya Zhan (PLoS ONE, 2016)
Heat shock proteins belong to a conserved protein family and are involved in multiple cellular processes. Heat shock protein 27 (Hsp27), also known as heat HSPB1, participates in cellular responses to not only heat shock, but also oxidative or chemical stresses. However, the contribution of HSPB1 to anti-oxidative response remains unclear. Here, we show that HSPB1 activates G6PD in response to oxidative stress or DNA damage. HSPB1 enhances the binding between G6PD and SIRT2, leading to deacetylation and activation of G6PD. Besides, HSPB1 activates G6PD to sustain cellular NADPH and pentose production in glioma cells. High expression of HSPB1 correlates with poor survivalrate of glioma patients. Together, our study uncovers the molecular mechanism by which HSPB1 activates G6PD to protect cells from oxidative and DNA damage stress.